Case report: EBV-related eye orbits and sinuses lymphohistiocytic infiltration responsive to rituximab in a patient with X lymphoproliferative syndrome type 1 - Giardino, Giuliana; Lanni, Vittoria; Mascolo, Massimo; Russo, Daniela; Cirillo, Emilia; Romano, Roberta; Cillo, Francesca; Grilli, Laura; Prencipe, Maria Rosaria; Iuliano, Adriana; Uccello, Giovanni; De Fusco, Carmela; et al. (Frontiers in Immunology, 2024)
Background and aims X lymphoproliferative syndrome type 1 (XLP1) is a rare inborn error of immunity due to mutations of SH2D1A, encoding for slam-associated protein (SAP). The clinical phenotype includes severe mononucleosis, hemophagocytic lymphohistiocytosis (HLH), and B-cell lymphomas. Methods We report the case of a child affected with XLP1 who presented with an incomplete HLH, triggered by Epstein–Barr virus (EBV) and treated with rituximab, involving orbits and paranasal sinuses. Results The lesion was indistinguishable from lymphoma, complicating diagnosis and treatment. In addition, considering the high incidence of lymphoma in patients with XLP1, histology helped define its nature, driving therapeutic choices. Conclusion We described an unusual presentation of incomplete HLH in a patient affected with XLP1: an EBV-driven infiltration of the orbits and paranasal sinuses. This led us to a challenging differential diagnosis of lymphoma-associated hemophagocytic syndrome, which can be frequently observed in patients with XLP1. Considering the extremely poor prognosis of this clinical finding, we sought for a prompt diagnosis and managed to obtain it and to immediately establish the right treatment on the basis of the pathological finding.